Studying the effect of Different wt % AL2O3 Nanoparticles of 2024Al Alloy / AL2O3 Composites on Mechanical Properties - Mohammed, Al-Alkawi Hussain Jasim; Al- Rasiaq, Abthal Abd; Al- Jaafari, Mamoon A. A. (Al-Khwarizmi Engineering Journal, 2019)
The nanocompsite of alumina (Al2O3) produced a number of beneficial effects in alloys. There is increasing in resistance of materials to surface related failures , such as the mechanical properties , fatigue and stress corrosion cracking .The experimental results observed that the adding of reinforced  nanomaterials  type Al2O3  enhanced the   HB hardness, UTS, 0.2 YS and ductility of 2014 Al/Al2O3 nano composites . the analysis of experiments, indicated that The maximum enhancement was observed at 0.4 wt.% Al2O3. The ultimate improvement percentage were 15.78% HB hardness, 18.1% (UTS), 12.86% (0.2 YS) and 25.71% ductility. These enhancements in the above properties maybe to high dislocation density resulting in good bounding between Al2O3 and metal matrix.